2017
DOI: 10.1149/2.0851714jes
|View full text |Cite
|
Sign up to set email alerts
|

XPS and SIMS Analysis of Solid Electrolyte Interphases on Lithium Formed by Ether-Based Electrolytes

Abstract: The chemical composition and microstructure of the solid electrolyte interphase (SEI) on lithium metal in ether-based electrolytes are investigated using X-ray photoelectron spectroscopy (XPS), time of flight secondary ion mass spectrometry (ToF-SIMS) and scanning electron microscopy (SEM). Electrolytes based on 1,2-dimethoxyethane (DME) and 1,3-dioxolane (DOL) solvents with lithium bis(trifluoromethane)sulfonamide (LiTFSI) conducting salt are employed to passivate lithium surfaces for different periods of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 34 publications
3
76
1
Order By: Relevance
“…All these components are well known to build up the SEI on metallic lithium anodes. [11,69,65,74] The additional line at 289.4 eV represents the (CF 3 ) group in LiTFSI [66] and is visible on all samples, presumably originating either from conducting salt residuals or LiTFSI decomposition. For all SEs analyzed in this study, the highest contribution of organic lithium salts is found in the binary mixture, while it is rather low for the single solvents.…”
Section: (6 Of 14)mentioning
confidence: 95%
See 1 more Smart Citation
“…All these components are well known to build up the SEI on metallic lithium anodes. [11,69,65,74] The additional line at 289.4 eV represents the (CF 3 ) group in LiTFSI [66] and is visible on all samples, presumably originating either from conducting salt residuals or LiTFSI decomposition. For all SEs analyzed in this study, the highest contribution of organic lithium salts is found in the binary mixture, while it is rather low for the single solvents.…”
Section: (6 Of 14)mentioning
confidence: 95%
“…It may originate from SE surface degradation due to unavoidable water traces in the LE. [65] Via complementary analysis of reference material it can be shown that the − CHO 2 fragment assigned to formate and − CHO 2,P , as a fragment of poly-DOL, are indeed distinguishable. [65] Compared to DME, we detect a significantly higher signal intensity for − CHO 2,P in the second region of the depth profile and assume that poly-DOL is a major constituent of the SLEI in DOL.…”
Section: (6 Of 14)mentioning
confidence: 99%
“…Identify the composition of the Li surface; Identify the composition of SEI in two different kind of electrolyte solvents;…”
Section: Characterization Of Li−metal Anodesmentioning
confidence: 99%
“…performed SIMS on Li−O 2 batteries cathode to confirm the reversible formation of Li 2 O 2 , Figure a . In addition, SIMS has another advantage of depth analysis, Figure b . Janek et al.…”
Section: Characterization Of Li−metal Anodesmentioning
confidence: 99%
See 1 more Smart Citation